How Distributed leadership Fosters Teacher Innovation: A Mediation Analysis of Self-efficacy and Professional Learning Communities - Wang, Hui (European Journal of Social Science Education and Research, 2026)
This research examines the links between distributed leadership and educator innovative behaviour, particularly as mediated by teacher self-efficacy and professional learning communities (PLCs), in junior high schools. The research draws on Social Cognitive Theory and Organisational Learning Theory, and considers a two-pronged model incorporating both psychological and organisational processes. This study utilized a quantitative approach, and information was gathered from teachers through a questionnaire. Partial Least Squares Structural Equation Modelling in SmartPLS was employed to analyse the data. Results show that distributed leadership  is positively associated with teacher innovation behaviour. Moreover, the Teacher Self-efficacy and PLCs is also a key mediator, suggesting that leadership drives innovation by boosting teachers' beliefs and fostering a culture of learning. The findings support partial mediation effects, underscoring the interaction between the individual and the group practices in promoting innovation. Our method adds to the existing body of related work by incorporating two mediators into a single model and offering empirical evidence. This research provides insights for Policymakers and school administrators to promote distributed leadership, improve the Teacher Self-efficacy, and establish professional learning communities to support innovative teaching practices.
Keywords: Distributed leadership, teacher innovative behaviour, self- efficacy, mediation analysis, educational leadership.